Modification and evaluation of a black pepper thresher - JINIL S NAVAS S SHAJI M. P; Er. Jippu Jacob (Guide) (Tavanur 2000 Kelappaji College of Agricultural Engineering and Technology)
Modification and evaluation of a black pepper thresher
Modification and evaluation of a black pepper thresher